Procalcitonin as Predictor of Bacterial Infection in Meconium Aspiration Syndrome - K., Mahendiran; Batra, Prerna; Faridi, M. M. A.; Singh, N. P. (American Journal of Perinatology, 2018)
Background There is a lack of definite consensus on indications for initiating antibiotics in neonates with meconium aspiration syndrome (MAS), instigating researchers to search for a biomarker that can help differentiate MAS from MAS with bacterial infection.Objective Our primary objective was to compare serum procalcitonin (PCT) levels in full-term vigorous neonates having MAS with or without bacterial infection.Materials and Methods Seventy term vigorous neonates with diagnosis of MAS were enrolled. Blood samples were taken for sepsis screen, C-reactive protein (CRP), PCT, and blood culture at 6 ± 2 hours of respiratory distress. Neonates were categorized into group 1 (MAS without bacterial infection) and group 2 (MAS with bacterial infection) based on blood culture. The duration of our study was 18 months.Results Mean ± standard deviation PCT level was 2.52 ± 3.99 in group 1 and 2.71 ± 4.22 in group 2, which was comparable. At cutoff of 0.1 ng/mL, PCT had a sensitivity of 90% and specificity of 8% in detecting bacterial infection. Mean total leukocyte count, absolute neutrophil count, immature to total leucocyte ratio, microerythrocyte sedimentation rate, and CRP were comparable.Conclusion Though PCT is an early and reliable marker of neonatal infection, the levels were increased in neonates with MAS irrespective of the presence of bacterial infection.
Keywords: meconium aspiration syndrome; neonatal sepsis; procalcitonin